2021
DOI: 10.1111/vco.12780
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of the cytosine deaminase::uracil phosphoribosyl transferase/5‐fluorocytosine suicide system for canine melanoma

Abstract: We tested the efficacy of a yeast cytosine deaminase::uracil phosphoribosyl transferase/5‐fluorocytosine (CDU/5‐FC) non‐viral suicide system on eight established canine melanoma cell lines. Albeit with different degree of sensitivity 5 days after lipofection, this system was significantly efficient killing melanoma cells, being four cell lines highly, two fairly and two not very sensitive to CDU/5‐FC (their respective IC50 ranging from 0.20 to 800 μM 5‐FC). Considering the relatively low lipofection efficienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(72 reference statements)
0
1
0
Order By: Relevance
“… 5 In addition, a recent study showed that the nonviral FCU1/5-FC system was effective against most of the assayed canine melanoma cell lines. 6 …”
Section: Introductionmentioning
confidence: 99%
“… 5 In addition, a recent study showed that the nonviral FCU1/5-FC system was effective against most of the assayed canine melanoma cell lines. 6 …”
Section: Introductionmentioning
confidence: 99%